2012
DOI: 10.1007/s00268-012-1494-3
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin Analogues for the Treatment of Enterocutaneous Fistulas: A Systematic Review and Meta‐analysis

Abstract: Somatostatin analogues appear to decrease the duration of enterocutaneous fistulas and duration of hospital stay, but no mortality benefit was identified. The quality of evidence for outcomes in this review ranged from low to moderate. Future large, blinded, RCT would be useful in improving the confidence in the treatment effects identified in this systematic review and meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 22 publications
(51 reference statements)
0
14
0
2
Order By: Relevance
“…Proton pump inhibitors and sucralfate were prescribed to decrease the acidity of the effluent and to potentially limit corrosive effects on skin. To control bilio-pancreatic output it was placed a catheter through the major duodenal papilla and it was administered octreotide, a long-acting somatostatin analog, which decrease fistula output by inhibiting secretion of various gastrointestinal hormones [ 16 , 17 ]. Skin barriers, adhesives (liquid, aerosol, and discs), dressings, and pouches were applied daily for protecting and maintain skin integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Proton pump inhibitors and sucralfate were prescribed to decrease the acidity of the effluent and to potentially limit corrosive effects on skin. To control bilio-pancreatic output it was placed a catheter through the major duodenal papilla and it was administered octreotide, a long-acting somatostatin analog, which decrease fistula output by inhibiting secretion of various gastrointestinal hormones [ 16 , 17 ]. Skin barriers, adhesives (liquid, aerosol, and discs), dressings, and pouches were applied daily for protecting and maintain skin integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on somatostatin (analogues) were performed to assess the effect on fistula closure rather than output reduction. Three recent systematic reviews and meta‐analyses on somatostatin (analogues) and ECF showed a potential benefit in time to closure and closure rate. However, this effect is most likely to be found in simple low‐output fistulas.…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43][44][45][46][47][48][49] Two recent meta-analyses summarize their results: somatostatin analogues and somatostatin do not improve mortality, but they seem to decrease fistula output, allow faster spontaneous closure, and decrease hospital stay. 50,51 The longest follow-up interval in studies is 90 days. 41 Somatostatin analogues versus control resulted in greater success of spontaneous fistula closure (relative risk [RR] 1.36) and shorter time interval to closure.…”
Section: Medical Management Of Fistula Outputmentioning
confidence: 99%